Gianotti-Crosti syndrome: a case report of a teenager - Renata Leite Pedreira; Juliana Martins Leal; Keline Jácome Silvestre; Alice Paixão Lisboa; Alexandre Carlos Gripp (Sociedade Brasileira de Dermatologia, 2016)
Abstract Gianotti-Crosti syndrome is a rare disease characterized by acral papular eruption with symmetrical distribution. It is a benign and self-limited disease; the symptoms disappear after two to eight weeks, without recurrences or scars. Skin lesions are usually asymptomatic. Prodrome might occur, suggesting upper respiratory infection, or constitutional symptoms. Diagnosis is eminently clinical, and this disease is associated with viral infections. Due to its rarity and low occurrence in adolescents and adults, we report a case of Gianotti-Crosti syndrome of a teenager.